2015
DOI: 10.1016/j.ijrobp.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Ion Irradiation Suppresses Migration and Invasiveness of Human Pancreatic Carcinoma Cells MIAPaCa-2 via Rac1 and RhoA Degradation

Abstract: In contrast to x-ray irradiation, C-ion treatment inhibited the activity of Rac1 and RhoA in MIAPaCa-2 cells and Rac1 in AsPC-1 and BxPC-3 cells via Ub-mediated proteasomal degradation, thereby blocking the motility of these pancreatic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…have recently demonstrated that heavy-ions could inhibit cell migration through downregulation of MMP-9 and upregulation of proadhesive cell surface integrin alpha-5 leading to increased cell adherence to extracellular matrix proteins [56]. Carbon ion is also known to reduce levels of GTP-bound Rac1 and RhoA, two important regulators of cell motility [57]. EGFR downstream signaling seems to be targeted by Carbon Ion in Lung Cancer [58], as in our study.…”
Section: Discussionsupporting
confidence: 77%
“…have recently demonstrated that heavy-ions could inhibit cell migration through downregulation of MMP-9 and upregulation of proadhesive cell surface integrin alpha-5 leading to increased cell adherence to extracellular matrix proteins [56]. Carbon ion is also known to reduce levels of GTP-bound Rac1 and RhoA, two important regulators of cell motility [57]. EGFR downstream signaling seems to be targeted by Carbon Ion in Lung Cancer [58], as in our study.…”
Section: Discussionsupporting
confidence: 77%
“…This increase in RBE is less about the effectiveness of carbon but more about the ineffectiveness of PhXRT with increased tumor grade (heterogeneity). In addition, unlike PhXRT which has been shown to enhance the migratory and invasiveness potential of various cancer cell lines, C-ions have consistently been shown to decrease cell migration, invasion, and matrix metalloproteinase activity across different cell lines and in in vivo tumor models [70,71,72,73,74,75,76,77]. CIRT has also been shown to modulate the immune response to tumors in mice [78,79] but very little work has been done so far on the interaction of heavy particle irradiation with the immune system.…”
Section: Preclinical Research In Carbon Ion Radiotherapymentioning
confidence: 99%
“…This impairs cellular ability for correct repair 25 and decreases the dependence of radiosensitization upon the presence of oxygen, desirable features for eradication of resilient, hypoxic tumors 5,26 . Further potential radiobiological advantages include greater RBE for killing putatively radioresistant cancer stem cells 27 and counteracting cancer invasiveness 28,29 , albeit the latter remains controversial 30 . Finally, low doses of high-LET radiation appear to elicit stronger immunological responses compared to low-LET radiation 16 .…”
Section: Introductionmentioning
confidence: 99%